2021
DOI: 10.1007/s10620-021-07316-4
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Biopsies of Solid Pancreatic Lesions: Tissue Acquisition Technique and Needle Design Do Not Impact Specimen Adequacy

Abstract: Background and Aims Data on adequacy of EUS guided biopsies using different tissue acquisition techniques and fine needle aspiration needle designs have been inconclusive. Data on newer fine needle biopsy (FNB) needles are scarce. This study compared the performance of 3 acquisition techniques and 2 fine needle biopsy designs in solid pancreatic lesions. Methods Single-center, randomized, pilot clinical trial (Trial registration number NCT03264092). Patients undergoing EUS biopsy of pancreatic lesions were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…As previously described for EUS-FNA 22 , slow-pull specimens resulted in lower blood contamination compared with wet-suction samples. This finding differs from the pilot study mentioned above, in which blood contamination was similar regardless of the sampling technique used 24 . However, the blood contamination score used was extremely simplified (score 0 = blood present and 1 = blood clots present), thus limiting the possibility of accurately differentiating and stratifying the results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As previously described for EUS-FNA 22 , slow-pull specimens resulted in lower blood contamination compared with wet-suction samples. This finding differs from the pilot study mentioned above, in which blood contamination was similar regardless of the sampling technique used 24 . However, the blood contamination score used was extremely simplified (score 0 = blood present and 1 = blood clots present), thus limiting the possibility of accurately differentiating and stratifying the results.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, for solid pancreatic lesions, tissue core procurement rate and tissue integrity score were similar between the two techniques. The present study seems to support the findings of a previous pilot study comparing wet suction with slow pull and standard suction for sampling of solid pancreatic lesions using end-cutting needles, where all three techniques resulted in similar histological yields 24 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, 16 RCTs [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] with 2048 patients were included in the meta-analysis. Figure 1 shows the PRISMA diagram for study selection.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The number of needle passes was two in majority of the studies [11,12,15,17,[19][20][21]23]. Six studies [15,16,20,[23][24][25] had moderate risk of bias while 10 studies had low risk of bias [11][12][13][14][17][18][19]21,22,26] (Supplementary Figure 1). The definitions of various outcomes used in the included studies in shown in supplementary Table 1.…”
Section: Accepted Manuscriptmentioning
confidence: 99%